Implementation of Aqidah Akhlak Learning Through the Burhani Approach in Islam Elementary School - Eka Tusyana (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This research aims to describe the implementation of learning Aqidah Akhlak through the Burhani approach at MI Wahid Hasyim. The method used in this research is a qualitative method with a descriptive approach. The instruments used in this study were interviews, observation, and documentation. The population used in this study was class IVA students, and the sample used in this study was 30 students. The subjects in this study were school principals, teachers, and students at MI Wahid Hasyim. The objectives of this study are 1) the implementation of the learning of moral principles and 2). Burhani approach at MI Wahid Hasyim. Analysis of the data used in this study, namely: a) data collection (data collection) b) data reduction (data reduction) c) data presentation (data display) d) concluding. The results of the study show that the implementation of learning aqidah morals through the Burhani approach at MI Wahid Hasyim on the sub-matter of obeying and obeying parents: first, obeying parents' advice by carrying out keeping the classroom environment clean. Second, love both parents by doing small things such as always loving the teacher as a substitute for both parents at home and loving their friends. Third, behave politely and politely by carrying out small things such as mutual respect for teachers or fellow friends. Fourth, being honest by carrying out small things such as when the teacher gives questions to be worked on by students and students work on these questions independently, and the teacher emphasizes students be honest such as not cheating on their friends. Through the Burhani approach, the learning process of aqidah akhlak familiarizes students to implement the learning material that has been obtained.